Halal critical point assessment for chicken broiler upstream operations - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Ajmain @ Jima’ain, Muhammad Talhah; Md Sikin, Adi; Jamaludin, Mohammad Aizat (Asian Scholars Network (ASNet), 2023)
Halal critical point (HCP) in the poultry business focuses has been only emphasized at the slaughter process and downstream production of chicken meat products. However, there is no extensive investigation on the implementation of HCPs at the upstream stage of broiler supply before it is transferred to halal slaughterhouses. This research aims to assess the halal critical point (HCP) involved in commercial broiler farming operations that might be halal critical, and therefore needs halal risk control. There are seven phase of operation in the broiler process, includes brooding, growth, feed withdrawal, medicine withdrawal, catching procedure, logistics, and slaughterhouse. The qualitative research approach using document analysis and semi-structured interview was used to gather more in-depth information and the halal critical controls were proposed. The findings of this research could assist the industry in maintaining the halal integrity of poultry-based products. Thus, enhance the halal authorities responsible for drafting halal development policy in the improvement of the halal management system along the broiler supply chain.